Structural, electrical and optical properties of Co3O4 nanoparticles - Makhlouf, Salah A.; Bakr, Zinab H.; Aly, Kamal I.; Moustafa, M.S. (Superlattices and microstructures, 2013)
•Co3O4 nanoparticles have been prepared by chemical precipitation method.•The XRD particle sizes are in a good agreement with those obtained by TEM.•The particles size and porosity depend on the calcination temperature.•Electrical measurements were done in a wide temperature range as functions of particle size.•Optical properties indicate a red shift of the absorption peaks relative to bulk Co3O4. Co3O4 nanoparticles were prepared by chemical precipitation followed by heat treatment at different temperatures. The structure and morphology of Co3O4 nanoparticles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, Transmission electron microscopy and the N2 adsorption–desorption techniques. The results indicate the formation of a single crystalline Co3O4 phase with a high surface area, mesoporous structure and particles size that depends on the calcination temperature. DC electrical conductivity was investigated in the temperature range 160–470K. Variation of the electrical conductivity with temperature reveals double-valued activation energy, and the data was discussed in view of the structural and morphological properties. The temperature dependence of the AC conductivity and dielectric constant was also investigated in the same temperature range. In addition, analysis of the optical properties indicates a red shift of the absorption peaks relative to bulk Co3O4.